Desired Traits of International Bus to Thai Tourists - เกียนวัฒนา, คมสิทธิ์; พานิชกุล, ธนพร; ณ นคร, พันทิวา; ช่วงสม, พีรัชชัยย์; โพธิ์ศรีเรือง, ธนวัต; แซ่นิ้ม, ธัญญาดา; ศรีคำภา, ปัณฑาวีย์; คงประเสริฐ, ศรัณย์; ธัญญะวนิช, อังคณา; เวียงวิเศษ, พจณิชา (Recent Science and Technology, 2019)
The purposes of this research were to study and to compare sex and income in terms of desired traits of international bus to Thai tourists. The data were analyzed statistically by frequency, percentage, means, standard deviation, content analysis, the test value “t” (t-test), and one-way analysis of variance: ANOVA. If the results had been significantly different in pairs, the Scheffe's Method would have been employed. The results were as followed; The desired traits of international bus of respondents had high levels in all aspects. The most desired was safety (= 3.82 S.D. = 0.972). Comparison the differences in the desired traits of international bus of respondents by gender, there was no significant difference in both male and female respondents at .05 levels. Comparison the differences in the desired traits of international bus of respondents by average monthly income interval, there was significant difference at .05 levels in information aspect.